2021
DOI: 10.1101/gad.348226.120
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and biological hallmarks of colorectal cancer

Abstract: Colorectal cancer has served as a genetic and biological paradigm for the evolution of solid tumors, and these insights have illuminated early detection, risk stratification, prevention, and treatment principles. Employing the hallmarks of cancer framework, we provide a conceptual framework to understand how genetic alterations in colorectal cancer drive cancer cell biology properties and shape the heterotypic interactions across cells in the tumor microenvironment. This review details research advances pertai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
158
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 282 publications
(168 citation statements)
references
References 417 publications
1
158
0
9
Order By: Relevance
“…Similarly, in colorectal cancer the identification of somatic mutations suggests a complex scenario where PTPRG can be modified quantitatively (reduced expression driven by methylation/non-coding RNAs) and qualitatively (somatic mutations), a feature shared with the alteration of other classic TSGs in cancer development. ( Capellini et al, 2021 ; Li et al, 2021 ). The case of Merkel Cell carcinoma is noteworthy, where integration of Merkel cell polyomavirus (MCV or MCPyV) to form different length fusions with intron 1 of the human PTPRG gene.…”
Section: Ptprg Interacts With Characteristic Oncogenes In Specific Cancer Typesmentioning
confidence: 99%
“…Similarly, in colorectal cancer the identification of somatic mutations suggests a complex scenario where PTPRG can be modified quantitatively (reduced expression driven by methylation/non-coding RNAs) and qualitatively (somatic mutations), a feature shared with the alteration of other classic TSGs in cancer development. ( Capellini et al, 2021 ; Li et al, 2021 ). The case of Merkel Cell carcinoma is noteworthy, where integration of Merkel cell polyomavirus (MCV or MCPyV) to form different length fusions with intron 1 of the human PTPRG gene.…”
Section: Ptprg Interacts With Characteristic Oncogenes In Specific Cancer Typesmentioning
confidence: 99%
“…Despite decades-long marker discovery efforts, currently dominated by larger-scale genomics and proteomics initiatives (reviewed in [ 54 , 55 , 56 , 57 ]), only a few molecular biomarkers of CRC are currently known and even fewer are clinically approved for medical use (reviewed in [ 6 ]) Traditional ‘omics’ technologies are perfectly capable of mechanistic sifting through tens of thousands of expressed genes and are routinely employed to find transcripts or proteins with altered expression patterns correlating with the disease in question. We aimed to explore a more rational approach to disease marker discovery.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in different types of cancer have demonstrated the critical roles of stromal cells in the tumor microenvironment in regulating cancer cell functions [31][32][33][34] . Moreover, studies from our group and others suggested that ECs, a critical but understudied component of the microenvironment, promoted cell survival in CRC and few other types of cancer by secreting paracrine factors (angiocrine) 12,28,35,36 .…”
Section: Discussionmentioning
confidence: 99%